CONGESTION CONTROL REAL-TIME PATH PLANNING IN HYBRID VANET FOR URBAN AREA - Mohan, Meera; Antony, Deepthi (IJRDO -Journal of Computer Science Engineering, 2015)
Real time path planning algorithm is aneffective way to avoid traffic congestion in urban areas. Itis challenging to develop an algorithm for path planning aseach driver has their own preferences while driving. Thereis existing Hybrid Intelligent Transportation System (ITS)for path planning and it is hybrid VANET enhanced ITS.This system utilizes vehicular ad-hoc network and cellularsystems of public transportation systems. With the help ofthis system, it is possible to have a real timecommunication between vehicles, road-side units (RSUs)and vehicle-traffic server. This system improves overallspatial utilization of a road network and reduces averagevehicle travel cost by avoiding it from getting stuck intraffic congestion. This is achieved by using real time pathplanning algorithm. Proposed system improvises the pathplanning algorithm by selecting the right path byconsidering the criticality of the vehicle (for e.g.,ambulance) and the type of the vehicle (a two wheeler canuse a narrow path when compared to the path that can beused for a car). By this approach, travel cost should comedown and also the spatial utilization should be even betterthan existing system